2019
DOI: 10.1093/geroni/igz038.3505
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation, Loneliness, and Caregiver Burden Among Paid and Unpaid Caregivers of Homebound Older Adults

Abstract: Caregivers of homebound older adults may have high levels of burden and more vulnerability to social isolation and loneliness, given that their care recipients are more physically frail and isolated. Existing literature has not fully investigated differences between paid and unpaid caregiver burden or their experiences of social isolation. We interviewed paid (n=21) and unpaid family caregivers (n=22) of homebound older adults in a hospital-affiliated geriatric house call program. We used validated survey inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…[23][24][25][26][27][28][29] This is particularly the case for those providing care for people with enduring brain conditions, due to social segregation, and cognitive and emotional deterioration of the care recipients, reflecting a dyadic impact. 4,5,[30][31][32][33][34] Pandemic-related restrictions have now exaggerated rates of loneliness and social isolation globally, 35 particularly in older people, 7,8,[36][37][38] women, 2,5,[39][40][41][42][43] and informal caregivers of people with enduring health conditions. 14,16,36,44,45 Informal caregiver status is an independent risk factor for increased loneliness during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28][29] This is particularly the case for those providing care for people with enduring brain conditions, due to social segregation, and cognitive and emotional deterioration of the care recipients, reflecting a dyadic impact. 4,5,[30][31][32][33][34] Pandemic-related restrictions have now exaggerated rates of loneliness and social isolation globally, 35 particularly in older people, 7,8,[36][37][38] women, 2,5,[39][40][41][42][43] and informal caregivers of people with enduring health conditions. 14,16,36,44,45 Informal caregiver status is an independent risk factor for increased loneliness during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Pre‐pandemic, loneliness in caregivers was associated with many adverse health outcomes, low quality of life, depression, and psychological distress 23–29 . This is particularly the case for those providing care for people with enduring brain conditions, due to social segregation, and cognitive and emotional deterioration of the care recipients, reflecting a dyadic impact 4,5,30–34 . Pandemic‐related restrictions have now exaggerated rates of loneliness and social isolation globally, 35 particularly in older people, 7,8,36–38 women, 2,5,39–43 and informal caregivers of people with enduring health conditions 14,16,36,44,45 .…”
Section: Introductionmentioning
confidence: 99%
“…Kokorelias et al (2020) described caregiving as a full‐time job and reported that caregivers struggle to manage time outside of caregiving. According to Sun et al (2019), caregivers of homebound care recipients are more susceptible to social isolation due to the frailty and dependence of the care recipient. This loneliness is linked to increased levels of stress and is a strong predictor of depression and overall well‐being (Vasileiou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced social interaction and travelling were experienced as they spent an average of 13 h a day on caregiving which meant they had less time available for interacting with others and travelling. All these factors may increase the risk of social isolation (Sun et al, 2019). Indeed, eight out of ten Muslim family caregivers in this study reported that they felt socially isolated while being family caregivers.…”
Section: Discussionmentioning
confidence: 99%